FAKTOR-FAKTOR YANG BERHUBUNGAN TINDAKAN PERSALINAN SECTIO CAESAREA DI RUMAH SAKIT SANTA ELISABETH SEMARANG - Wulandari, Priharyanti; Maharani, Ratna Puri; Arifianto, Arifianto (Universitas Muhammadiyah Magelang, 2018)
Sectio caesarea (SC) is surgical action for give birth by opening lower abdomain and uterus.Sectio Caesarea is used as the last choice that caused by various difficulties such as prolonged babybirth, Uteri imminens rupture, placenta previa, big fetus, pre eclamption and bleeding. Sectio Caesarea also have a high risk for mother and also the babies, but in the fact sectio caesarea level is going bigger in many countries including Indonesia.This research is usingRetrospektif data, total sample in this researchis 62 respondent taken by total sampling technique. Data is taken by observation sheet, then this data is tested by using Chisquare statistic test.Based on analysis result using Chisquare statistic test, the result ofgestational age obtainedP Value= 0,027, Mother age obtainedP Value = 0,014, Sectio Caesarea profile obtainedP Value= 0,003, Comorbidities obtainedP Value= 0,004. Partial trials are allowed in women with a history of SC more than once the results are good and the complications are minimal. It is preferable for women with a history of SC to first determine the type of previous section.